Desarrollo de un PLC-ESP32 Open Source Didáctico con 23 E/S para el programa de Ingeniería Electrónica Uan-Neiva (2023)
In the academic and practical training of electronic engineering at the Antonio Nariño University Neiva campus (UAN-Neiva), the importance of interdisciplinarity in learning is highlighted, especially in subjects related to Industrial Automation. These subjects require updated teaching tools to guarantee quality education. In this context, an educational Programmable Logic Controller (PLC) based on ESP32 was developed. This educational PLC, consisting of 23 inputs/outputs, will be a practical and accessible tool designed to improve students' skills in programming languages widely used in the commercial PLC industry, such as Ladder Logic, Structured Text, Function Block Diagram, Instruction List, among others.